Employee Perception on Corporate Social Responsibility and Job Satisfaction in Large Scale Units - Vyas, J. H.; Shrivastava, Reshma (Prabandhan: Indian Journal of Management, 2011)
Corporate Social Responsibility is basically a business's response to new conditions, new challenges and new opportunities(Tom Bateman,2003).The idea of CSR is very old, and it has been successfully implemented in many of the companies at the world level and also in India. Some of the major drivers of CSR in India have been Tata's, Birla's SAIL, ONGC, NTPC and so on. What are these companies doing under CSR? - they are returning to the stakeholders, what they are receiving. The new mantra for today's corporates has been to serve people. We cannot deny the truth that employees are the true assets, so companies need to focus on building the Employee base at every single level. As the role of the HR department has undergone a tremendous change, the value proposition of HR should also change, and it has to develop to meet the demands of the changing environment. CSR is no more a new concept , companies are now focusing on investing in employees, and now they know that this brings direct benefits to a company both financially and in terms of increased employee loyalty and productivity. The basic focus of this paper is to make CSR activities the base of developing Employee Participation and ultimately, measuring the effectiveness of CSR activities from the employees' perspective. The paper looks at the areas where employees can truly be participative , the employees' views towards CSR, and how to promote CSR activities so that employess feel happy and satisfied to be the part of socially responsible companies. Thus, the basic purpose of the paper is to verify the importance of CSR programs and activities and Employee job related outcomes for large-scale sector companies in Chhattisgarh.